The Domestic Church (Hekima Review, 2014)
Lumen Gentium 11, describes the family as a domestic church. This description, in a big way, puts the family as the centre of the day to day Christian activity. It is not easy to tell whether this important reality of the contemporary Church is in crisis or in progress as each person will be judging it based on what one believes or on the trend one leans on. The liberals’ ideas will definitely differ from those of the conservatives. However, each of them is entitled to their opinion as the teaching of the Church is there to guide regardless of the trend one takes.